2018
DOI: 10.1039/c8sc02279h
|View full text |Cite
|
Sign up to set email alerts
|

Silylated cyclopentadienes as competent silicon Lewis acid catalysts

Abstract: Silicon Lewis acid donor catalysts incorporating highly electron-deficient cyclopentadienes are shown to catalyze C–C bond formation via anion abstraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…However, no attempts have been made to modify them to increase the catalytic activity. Silicon Lewis acids were obtained from cyclopentadienes with ester groups, the presence of which made it possible to modify these acids in order to increase their catalytic activity [81].…”
Section: Ohmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no attempts have been made to modify them to increase the catalytic activity. Silicon Lewis acids were obtained from cyclopentadienes with ester groups, the presence of which made it possible to modify these acids in order to increase their catalytic activity [81].…”
Section: Ohmentioning
confidence: 99%
“…Radtkea and Lambert [81] showed that N-benzyland N-allylindoles reacted with high yields, whereas the yield with indole intelf was moderate. The alkylation of 1,3-dimethoxybenzene led to product 97f with a yield of 80%.…”
Section: Ohmentioning
confidence: 99%
“…These pentacarboxycyclopentadienes (PCCPs) have been used as cyclopentadienyl‐type ligands [40–42] in coordination chemistry. They served as a novel class of enantioselective Brønsted acid catalysts [43] and Lewis acids [44] . However, to the best of our knowledge, their potentially chelating carboxylate groups have never been used to bind a metal, e. g. next to a different (hetero)metal bound to the η 5 ‐cyclopentadienyl carbanion.…”
Section: Introductionmentioning
confidence: 99%
“…[22] To address this issue, we proposed that attenuation of the PCCP anion basicity would inhibit deprotonation and allow access to larger-molecular-weight polymers while maintaining the insensitivity of these polymerizations to moisture and nucleophilic impurities. This goal could be achieved through either modulation of the PCCP structure [23,24] or through additives that interact with the PCCP anion at the chain end. We chose to pursue the second approach because of the modularity of this strategy.…”
mentioning
confidence: 99%